Essays on Financial Integration, Inequality, and Geoeconomics - Yun, Jinyeong; Justus Liebig University Giessen (My University, 2026)
In the first paper, I document empirical evidence indicating that an exogenous capital inflow shock increases income inequality in advanced economies and reduces income inequality in emerging market economies. To examine the effects of capital inflows on income inequality within countries, I estimate a panel structural vector autoregression model with annual data for 53 countries over the period 1990 to 2020. I identify the structural shocks in capital inflows using sign restrictions, thereby distinguishing the exogenous shocks driven by global financial conditions from other shocks. The findings of this paper indicate a remarkable difference in the results between advanced economies and emerging market economies, suggesting that the distributional effects of capital inflows vary depending on the economic conditions in the recipient countries. With respect to income class, a capital inflow shock is primarily associated with an increase in the income share of the high-income class in advanced economies and of the low-income class in emerging market economies. It is necessary for policymakers to pay attention to the distributional effects of capital inflows and to design tailored policy frameworks to address them. The second paper in the dissertation provides novel empirical evidence by examining the impact of financial integration on wage inequality using an unbalanced panel for 20 European countries from 1999 to 2021. Focusing on between-firm wage inequality within industries arising from firm heterogeneity, I find that financial integration (capital flows) increases wage inequality within industries. The effects are more pronounced in the medium term rather than in the short term. The paper then uncovers the underlying mechanism in the distributional effects of financial integration. I show that financial integration shocks widen the capital intensity (the capital-to-labor ratio) gap between firms within industries, which in turn widens the labor productivity gap. This channel allows highly productive, capital-intensive firms to increase wages to a greater extent than small and medium-sized enterprises (SMEs). This proposed channel is further validated by showing that the adverse distributional effects of capital flows are more pronounced in industries with a higher degree of external financial dependence. Finally, while deeper domestic financial markets may play a mitigating role, this effect appears secondary to external financial dependence. Geopolitical risk is commonly associated with adverse outcomes in financial and commodity markets. The third paper shows that the projection of military power in response to geopolitical risk can generate positive financial market responses. We examine the effects of unexpected increases in the presence of the U.S. military in East Asia on asset prices and capital inflows in the region. To this end, we construct a novel index from local newspapers reporting on the presence of U.S. Carrier Strike Groups (CSG) and assess the causal effects of a surprise change in this index on financial markets. Our findings reveal that a higher military presence leads to an increase in stock prices, an appreciation of the local currency, and an inflow of foreign capital. We also document substantial heterogeneity in the effects across geopolitical contexts and U.S. administrations. Market responses are strongly positive when deployments of CSG pertain to North Korean provocations, but muted or even negative when related to tensions with China. Moreover, the expansionary effects disappear or change sign during the first Trump administration, suggesting that the market benefits are tied to overall U.S. strategic policy frameworks. Our findings underscore that the projection of U.S. military power can function as a stabilizing signal for local financial markets, but only under specific geopolitical and institutional conditions.
Keywords: Financial integration; Capital flows; Economic inequality; Financial markets; Geoeconomics; ddc:330